Design of nano-slot waveguides with enhanced sensitivity and high coupling efficiency / Nor Aina Che Manaf - Che Manaf, Nor Aina (2016)
This thesis focuses on the simulation of light wave propagation, particularly in electric field discontinuity in silicon nano-slot waveguide, which include design of vertical and non-vertical nano-slot waveguides and also investigation of an efficient fiber coupling to vertical nano-slot waveguide. A silicon slot waveguide structure allows high optical confinement to propagate through a low index region of the waveguide. The photonic softwares used in this thesis are FIMMWAVE, KALLISTOS and FIMMPROP from Photon Design that is based on Film Mode Matching (FMM), Finite Element Method (FEM) and also Eigenmode Expansion Method (EME) for 3D optical propagation design. The FMM mode solver shows to be the best choice in modelling and obtaining the modal characteristics of vertical and horizontal waveguide structures. Verifications of FMM technique were done using FEM approach that give moderately similar mode fields and the rigorous solution are also in a good confirmation with the other previous studies. In the design approach, the semi-analytical technique using optimizer KALLISTOS have been adopted which allows fast optimization process. In the design and simulation of vertical and nonvertical nano-slot waveguide, a full vectorial FMM and FEM methods were used respectively in solving the problem of different high index contrast waveguide structures. Propagation analysis of fiber to inverted taper slot waveguide coupling was conducted by FIMMPROP using finite element-eigenmode expansion (FE-EME) method. Basically, all the objectives set in the thesis were achieved. In the investigation of optimized slot waveguide structures, a maximum power confinement factor of the TE mode was established at different cover media for homogeneous sensing application. As for a high optical confinement factor at standard height, H = 300 nm, it were found to be 68%, 89% and 86% for air, water and Si02 cover media with optimized W = 210 nm and WSb = 80 nm for vertical slot waveguide. Similarly, an optimized non-vertical slot waveguide design was obtained at about 60%, 79% and 81% with slanted sidewall angle of 28.1° at W = 100 nm, Wr = 260 nm, Wsb = 80 nm and Ws = 240 nm. The waveguide sensitivity of optimized vertical and non-vertical slot waveguide with a maximum calculated confinement factor in cover medium were also examined. It has a waveguide sensitivity of air, water and Si02 cover of about 1.000, 0.90 and 0.8666 used for vertical slot waveguide, while 0.64637, 0.76164 and 0.81483 for non-vertical slot waveguide, respectively. Finally in this thesis, optical coupler of inverted taper based fiber to vertical slot waveguide were proposed and investigated. In the investigation of fiber adapted waveguide based on inverted taper structure, the effect of taper tip width and taper length are observed to be one of the main parameter for matching mode size from optical fiber. And in the proposed of an efficient slot waveguide coupler, a fiber adapted waveguide of SU8 polymer with a dimension Wp = Hp = 2|um give a slightly larger fiber MFD of 2.9 |im to be match with an inverted taper tip width of 60 nm and length of 50 )nm, thus achieved a total coupling efficiency of 93%.